Bioethanol Production from Oil Palm Empty Fruit Bunches Using R5I3 Isolate Immobilized on Sodium Alginate Beads - Ida Bagus Wayan, Gunam; Yanti Sinurat, Dame; Wartini, Ni Made (Graduate School, Universitas Brawijaya, 2025)
Indonesia is the world's largest palm oil producer, contributing 59% of the total global production. The decreasing availability of fossil fuels contrasts with the increasing energy demand due to population growth. The development of bioethanol as an alternative energy source is expected to replace fossil fuels while contributing to environmental sustainability. Oil palm empty fruit bunches (OPEFB) are abundant industrial waste which is a potential raw material for bioethanol production. This study aims to analyze two different R5I3 cell treatments and fermentation time on bioethanol production from OPEFB and to determine the type of cell and fermentation time that produces the highest bioethanol content. The experiment was conducted using a Randomized Block Design with two factors: cell treatment types (free and immobilized cells) and fermentation time (24, 48, 72, and 96 hours). The results showed that cell treatment types significantly affected reducing sugar content, pH, total dissolved solids, and ethanol concentration. Fermentation time influenced reducing sugar content, total dissolved solids, and ethanol concentration but had no significant effect on pH. The treatment of immobilized R5I3 cells with a fermentation time of 72 hours produced bioethanol with the highest ethanol content of 1.02% (v/v).